2020
DOI: 10.1007/s10530-020-02345-y
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated invasion of decapod crustaceans in the southernmost point of the Atlantic coast of Europe: A non-natives’ hot spot?

Abstract: 16 17 Observations of previously unrecorded non-native species in the Gulf of Cadiz (Spain), situated 18 between the Atlantic Ocean and the Mediterranean Sea, have accelerated since 1980, and 19 increased rapidly in the past five years. Four new records of decapod crustaceans have been 20 detected in this region: the African snapping shrimp Alpheus sp., the West African cleaner shrimp 21 Lysmata uncicornis, the Indo-West Pacific giant tiger prawn, Penaeus monodon, and the Atlantic 22 blue crab Callinectes sapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Finally, climate warming will expand northward along the European Atlantic coast through the gulf of Cadiz and will benefit non-native species with wide environmental tolerances, as has already occurred with other macroinvertebrates [1].…”
Section: Climate-related Invasion Of Non-native Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, climate warming will expand northward along the European Atlantic coast through the gulf of Cadiz and will benefit non-native species with wide environmental tolerances, as has already occurred with other macroinvertebrates [1].…”
Section: Climate-related Invasion Of Non-native Speciesmentioning
confidence: 99%
“…New worldwide observations of non-native invasive species (NIS) have increased over time, for instance in the Gulf of Cadiz (Spain), GoC, since 1980 and even more in the last five years [1]. Although the rate of new observations cannot be relied upon as an indicator of introduction rate, due to such factors as: sampling bias, occurrence of unexpected discoveries, lag time between introduction and discovery, and high variability in sampling effort, it does indicate increasing pressure on the GoC.…”
Section: Introduction: An Increase In the Arrival Of Speciesmentioning
confidence: 99%
“…The most prominent humanmediated dispersal vectors in aquatic ecosystems are intentional introductions, aquaculture, and shipping/boating (e.g., ballast water, hull fouling) (Gollasch, 2006;González-Ortegón et al, 2007;Cuesta et al, 2016). The invasion of exotic species is being accelerated worldwide as a consequence of expanding transport and commerce (Mack et al, 2000); for instance, non-native species have been reported in the Gulf of Cadiz since 1980, but have increased rapidly in the last five years (González-Ortegón et al, 2020). The so-called Atlantic blue crab Callinectes sapidus Rathbun, 1896, a species native to the western Atlantic Ocean, is a good example for the introduction and fast growth of new non-native populations in the Euro-African area (Nehring, 2011;Mancinelli et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…On the western coast of the Iberian Peninsula, the first record dates back to 1967 in the Tagus Estuary (Portugal), but only a few sporadic records were made since then in this region (Encarnação et al, 2022). Along the Mediterranean coast of the Iberian Peninsula, the first record was made in the Ebro Delta in 2012-2013 (Castejón & Guerao, 2013), and since then its distribution expanded rapidly towards the Strait of Gibraltar where it has been registered since 2017 (Cabal et al, 2006;Nehring, 2011;Mancinelli et al, 2017a;Mancinelli et al, 2017b;González-Ortegón et al, 2020;Mancinelli et al, 2021). In the Gulf of Cadiz, the first published record of Atlantic blue crab dates back to 2016 (Morais et al, 2019), however, a male adult specimen was already collected in the Guadalquivir Estuary in 2002 (Rodríguez & Cuesta, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation